2012
DOI: 10.1186/2228-5326-2-26
|View full text |Cite
|
Sign up to set email alerts
|

Designed plasmonic nanocatalysts for the reduction of eosin Y: absorption and fluorescence study

Abstract: In this work, we report a one-step green synthesis of gold nanoparticles (AuNPs) by microwave irradiation using nontoxic and biodegradable polysaccharide chitosan as a reducing and stabilizing agent. The interaction between gold nanoparticles with the amine group of chitosan was confirmed by Fourier transform infrared spectroscopy analysis, and the stability of the nanoparticle is ascertained by zeta potential measurements. Transmission electron microscopy photograph and dynamic light scattering measurements c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 42 publications
6
14
0
Order By: Relevance
“…The rst minor peak centered on the diameter of 23 nm attributed to the formation of chitosancapped AuNPs, and the major peak (at 308 nm) suggests the presence of CAuNC in the solution. The particle size of CAuNC could be vary with the synthesis method, however, similar particle size distribution prole of CAuNC has been reported by Komalam et al 32 The particle size of CAuNC obtained by zetasizer analysis was considerably higher than that of FE-TEM analysis. This variation could be due to the formation of chitosan hydrogel shell in the aqueous solution.…”
Section: Synthesis and Characterization Of Cauncsupporting
confidence: 78%
See 1 more Smart Citation
“…The rst minor peak centered on the diameter of 23 nm attributed to the formation of chitosancapped AuNPs, and the major peak (at 308 nm) suggests the presence of CAuNC in the solution. The particle size of CAuNC could be vary with the synthesis method, however, similar particle size distribution prole of CAuNC has been reported by Komalam et al 32 The particle size of CAuNC obtained by zetasizer analysis was considerably higher than that of FE-TEM analysis. This variation could be due to the formation of chitosan hydrogel shell in the aqueous solution.…”
Section: Synthesis and Characterization Of Cauncsupporting
confidence: 78%
“…33 Meanwhile, zeta potential of AE30 mV is required to create the physically stable nano-suspension, which is stabilized by electrostatic repulsion. 32 Zeta potential of CAuNC was +37.45 AE 1.25 mV, which suggested that the prepared CAuNC was moderately stable. Moreover, zeta potential has been suggested as a key factor that contributes to the antifungal effect of chitosan through the interaction with negatively charged microbial surface.…”
Section: Synthesis and Characterization Of Cauncmentioning
confidence: 92%
“…Gelatin-stabilized Au nanoparticle was used for the catalytic reduction of xanthenes type dyes (Tagar et al 2012). Komalam et al (2012) reported the catalytic reduction of Eosin B in the presence of chitosan stabilized Au nanoparticles. Similarly, other nanocatalysts were used for the degradation of xanthenes type dyes (Junejo and Baykal 2014;Deka et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Under acidic conditions, the chitosan gets hydrolyzed and the glucosamine ring is opened. When Au 3+ ions were introduced into the acidic solution of chitosan, the Au 3+ ions oxidized the glucosamine to glucosamino acid [29,30]. Simultaneously, gold (III) was reduced to chitosan-capped nanoparticles.…”
Section: Ft-ir Studiesmentioning
confidence: 99%